Efektivitas Model Discovery Learning Pada Materi Tata Surya Kelas VII - istifadatun na'imah; Nur Kuswanti; Andri Wahyu Wijayadi (Universitas Islam Madura, 2019)
Currently learning in schools uses the curriculum 2013. This study aimed to describe the effectiveness of the discovery learning model in the Solar System matter based on teacher activities, student learning activities, learning outcomes, and student responses. The research used one-shoot case study with getting a sample using purposive sampling. The sample used was class VII B. The study was conducted in the even semester of the academic year 2018-2019. The effectiveness of learning was determined based on four indicators including the implementation of discovery learning based on teacher activities and student learning activities, student learning outcomes, and student responses. If the four indicators got good minimum criteria, the learning was effective. Based on the results of the research, teacher activities in learning reached 100%, student activities in learning reached 83,6%, completeness of student learning outcomes was 40% were 9 from 15 students didn’t complete, completeness of learning indicators reached 50% and positive responses of students to discovery learning models was 94%. Thus, it can be concluded that the discovery learning model is less effective in the VII grade Solar System material because one indicator did not get minimum criteria either. Keywords: Discovery Learning, Effectiveness, Solar System Abstrak: Pembelajaran di sekolah-sekolah saat ini mengikuti kurikulum 2013. Pendekatan yang sesuai dengan kurikulum 2013 adalah discovery learning yang memberikan siswa kesempatan untuk menemukan konsep sendiri. Tujuan penelitian ini untuk mendeskripsikan efektivitas model discovery learning pada materi Tata Surya berdasarkan aktivitas guru, aktivitas siswa, hasil belajar, dan respon siswa. Rancangan penelitian yang digunakan adalah one-shoot case study dengan pengambilan sampel secara purposive sampling. Sampel yang digunakan adalah kelas VII yang berjumlah 15 orang. Penelitian dilaksanakan pada semester genap tahun ajaran 2018-2019. Keefektifan pembelajaran diukur dengan empat indikator meliputi aktivitas guru, aktivitas belajar siswa, hasil belajar siswa dan respon siswa. Jika keempat indikator tersebut memiliki kriteria minimal baik, maka pembelajaran dikatakan efektif. Hasil penelitian ini menunjukkan bahwa aktivitas guru dalam pembelajaran terlaksana 100%, kesesuaian aktivitas siswa dengan tahap-tahap dalam rencana pembelajaran sebesar 83,6%, ketuntasan hasil belajar siswa sebesar 40% dimana 9 siswa dari 15 siswa tidak tuntas, dan ketuntasan indikator pembelajaran sebesar 50% karena 2 dari 4 indikator pembelajaran tidak tuntas serta respon positif siswa terhadap model discovery learning sebesar 94%. Dengan demikian , dapat disimpulkan bahwa model discovery learning kurang efektif digunakan pada materi Tata Surya kelas VII karena salah satu indikator tidak memiliki kriteria minimal baik.